Answer:
8x²- x -8
Step-by-step explanation:
The question is not well written. I guess what you mean is:
Subtract -2x^2+4x-1 ( minus 2x squared plus 4x minus 1) from 6x^2+3x-9 (6x squared plus 3x minus 9).
To subtract -2x^2+4x-1 from 6x^2+3x-9, that is
6x^2+3x-9 - (-2x^2+4x-1). This can be written as
6x²+3x-9 - (-2x²+4x-1)
Now, opening the bracket, we will get
6x²+3x-9 +2x²-4x+1
Then, collecting like terms, we get
6x²+2x²+3x-4x-9+1
6x²+2x² = 8x²
3x-4x = -x
-9+1 = -8
∴6x²+2x²+3x-4x-9+1 becomes
8x²-x -8
The answer is 8x²-x -8.
Answer:
11%
Step-by-step explanation:
1/3 (twix)
1/3 (snicker)
1/3 x 1/3 = 1/9
1/9 = .11
.11 = 11%
Answer:
C
Step-by-step explanation:
well if you multiply each of tjem you would only sabe money on c the other choices would cause you to lose money so its c
Answer:
P(B and D) = 0.35
Step-by-step explanation:
It is a probability tree diagram. Here to find P(B and D):
apply method:
P(A and B) = P(A) × P(B)
Here given:
So, P(B and D):
Answer:
L x W x H
Step-by-step explanation:
Find area of one plane, then multiply by the prism's height.